2019
DOI: 10.1108/ijoa-12-2017-1311
|View full text |Cite
|
Sign up to set email alerts
|

An exploration into the understanding of football value chain in south of Brazil

Abstract: Purpose Football is significant in the global economic context. However, the same significance is not identified in the value added to the chain, as the elements that make it up act in a disintegrated and independent manner with undesired effects. Consequently, it is necessary to structure the undesired effects to seek the basic causes that sustain this problematic situation. Thus, this paper aims to use a CRT to structure the undesired effects and basic causes that limit the positive economic impacts of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…In line with Serrano et al (2019b), we found that football SCM integrative perspective can help the football clubs to make more profit. Football industry can generate many profits, such as millions of job opportunities, interactions with sponsors, healthy entertainments development, positive cultural effects on the society, internationally sense of belonging for clubs' fans (Marquetto et al, 2017;Memari et al, 2020).…”
Section: Managerial Implicationssupporting
confidence: 78%
“…In line with Serrano et al (2019b), we found that football SCM integrative perspective can help the football clubs to make more profit. Football industry can generate many profits, such as millions of job opportunities, interactions with sponsors, healthy entertainments development, positive cultural effects on the society, internationally sense of belonging for clubs' fans (Marquetto et al, 2017;Memari et al, 2020).…”
Section: Managerial Implicationssupporting
confidence: 78%
“…Thus, it is necessary to reduce the performance of intermediary agents and effectively manage the club, avoiding the early commercialization of athletes. This happens prior to the economic return invested in its formation, as pointed out by the CRT (Serrano et al, 2019b) and systemic structure (Serrano et al, 2018). By analyzing the "Current" scenario under the leverage point "investment in junior categories," the current club policy is identified as positive, as the results of the AVS earned by third parties with the club are positively impacted by it.…”
Section: Discussionmentioning
confidence: 98%
“…Given this result, it is possible to infer that investment in junior categories has a positive impact on the financial economic results of the club and third parties. Therefore, the "investment in junior categories" can be considered a leverage point (Serrano et al, 2019b), as there is "economic participation generated by the club in society" (key variable), that is, there is addition of value. The values of the scenarios corroborate the links identified, which attributes the benefits of the club with the athlete to two reasons.…”
Section: Graph 2 Effects Of "Investment In Junior Categories" -Hotel ...mentioning
confidence: 99%
See 2 more Smart Citations